The Effects of Using Educational Videos in Online Learning: A Case Study for Basic Computer Science Subject - Ramly, Noraliza; Rosli, Ahmad Nurzid; Suhaimi, Suhazlan; Abd Wahab, Mohd Helmy; Ariffin, Asma Hanee (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2023)
This study was conducted to examine the effect of the use of educational videos in online learning which can attract students and help students understand the topic of learning more effectively. A quantitative design with a survey method was used in this study. The respondents of the study consisted of 43 teachers of Basic Computer Science subjects in the state of Perak who were selected by random sampling. A questionnaire form instrument was used to collect data based on a five-point Likert Scale. Data were analyzed by descriptive analysis where the mean amount was determined based on a predetermined level. The results show that the use of educational videos can help students understand the topics of learning effectively with an average mean value = of 4.40. In addition, educational videos also help attract students to learning topics with an average mean value = of 4.30. The implications of this study indicate that the use of educational videos in online learning is proven to have a positive impact on students.